Visiting Frances Kamp in San Mateo - Watkins, Howard::::::::: (1980)
Frances Kamp, Christine Watkins holding Adam Watkins, Fran's brother Carleton "Stretch" Elliott Carleton played for Green Bay Packers in mid-1950's